Steam gasification of a thermally pretreated high lignin corn stover simultaneous saccharification and fermentation digester residue. (15th January 2017) - Howe, Daniel T.; Taasevigen, Danny; Garcia-Perez, Manuel; McDonald, Armando G.; Li, Guosheng; Wolcott, Michael
Abstract: Efficient conversion of all components in lignocellulosic biomass is essential to realizing economic feasibility of biorefineries. However, lignin cannot be fermented using biochemical routes. Furthermore, high lignin and high ash residues from simultaneous saccharification and fermentation (SSF) is difficult to thermochemically process due to feed line plugging and bed agglomeration. In this study a corn stover SSF digester residue was thermally pretreated at 300 °C for 22.5 min and gasified in a fluidized bed gasifier to study the effect of thermal pretreatment on its processing behavior. Untreated, pelletized SSF residue was gasified at the same conditions to establish the baseline processing behavior. Results indicate the thermal pretreatment process removes a substantial portion of the polar and non-polar extractives, with a resultant increase in the concentration of lignin, cellulose, and ash. Feed line plugging was not observed, although bed agglomeration occurred at similar rates for both feedstocks, suggesting that overall ash content is the most important factor affecting bed agglomeration. Benzene, phenol, and polyaromatic hydrocarbons in the tar were present at higher concentrations in the treated material, with higher tar loading in the product gas. Total product gas generation is lower for the treated material, although overall gas composition does not change. Highlights: High lignin residue from SSF process was pretreated at 300 °C for 22.5 min. TPT residue was gasified at nominal gasifier temperature of 895 °C. Untreated residue was gasified at same conditions to provide baseline. Total gas evolution of TPT material was only 64% of untreated material. Feed line plugging did not occur, but bed agglomeration was still taking place.